Virtualization: Blessing or Curse? - KOTSOVINOS, EVANGELOS (Communications of the ACM, 2011)
The article examines the potential benefits and detriments of virtualization. While it has been championed as a solution to numerous computing problems, including data-center optimization and carbon emission reduction, the author attests that there are hidden costs inherent in virtualization, stemming from the difficulty level of system administration. The process is intended to run the same workload as a virtual machine, but on fewer servers, thereby improving server utilization and enhancing the manageability of an enterprise infrastructure. The author urges that vendors offering virtualization must amend the prototype before it can become cost-effective.